Teacher views on barriers to the integration of information and communication technologies (ict) in Turkish teaching - Özdemir, Serpil; Özdemir, Serpil (Look Academic Publishers, 2017)
Technology has taken place in all areas of life. Educational environment is equipped with the technology to educate individuals with the skills to meet the needs of the day. It is expected that teachers use information and communication technologies and transfer this skill to the educational environment in the information age. When the use of ICT addressed in the context of the specific area the advantages and problems can be clearly evident. The purpose of this research is to identify barriers to the integration of ICT in Turkish teaching. Qualitative research method was adopted in the research. Participants were determined by criteria sampling method. 14 Turkish teachers who work in public schools in Bartın city center have participated in the research. The interview form was used as data collection tool. The data obtained from the interviews was conducted content analysis. Eight themes that prevent Turkish teachers from using ICT in Turkish lessons were identified. These themes are "inadequacy of technology infrastructure of the school, ICT inadequacy of the teacher, not directing the program to ICT, not being suitable for Turkish lessons, habit, loss of time, inadequacy of course materials for Turkish lesson, and ICT inadequacy of students". The participants' solution suggestions are based on the following themes: developing the ICT infrastructure of the school, practical training for the use of ICT in Turkish lessons, directing the program to ICT, developing the ICT information and equipment of the student.
Keywords: Teaching Turkish; ICT integration; Teacher views